Nutrition, information and risk factors for development of cardiovascular diseases in a segment of high school youth in the Republic of Macedonia - Mitrevska, Suzana; Georgievska-Ismail, Ljubica; Georgiev, Antonio (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2013)
The findings so far about the increasing prevalence of risk factors for occurrence of cardiovascular diseases in particular, which are a leading cause of mortality worldwide, as well as the fact that atherosclerosis begins in childhood, points to the need of urgent preventive measures at an early age. Aim of the study: Assessment of the eating habits, awareness and knowledge of risk factors for the occurrence of cardiovascular diseases among the high school population in RM. Materials and methods: A cross-sectional study was made in the period January – June 2011. The sample comprised of 347 respondents, students in the 4th year, aged 17-18 years, from a total of 9 high schools in RM. A structured questionnaire was prepared for the purpose of gathering the necessary data. The SPSS16.0 programme was used for statistical processing of the data. The following statistical methods were used: distribution of continuous variables, distribution of categorical variables; for testing the significance of the differences in the distribution of the obtained answers on the continuous variables, depending on the obtained distribution: t-test for independent samples. A statistical significance was determined as a p value <0.05. Results: The survey showed that the high school students in RM have poor eating habits, 57.6% eat fast food, 36.9% are overweight, 32.6% usually eat red meat and 29.4% eat processed meat several times a week, 36.6% eat fish only once a month, 57.1% are partially informed about the risk factors that lead to cardiovascular diseases etc. Conclusion: The partial information of the high school students on healthy nutrition and risk factors for cardiovascular diseases should motivate us to work harder on the health education in the schools.
Исхрана, информираност и ризик фактори за развој на кардиоваскуларните заболувања кај сегмент од средношколската младина во Република Македонија
Keywords: cardiovascular diseases; nutrition; lifestyle; adolescents